Development of new lean manufacturing approach through people development and process improvement as a mediator in the libyan companies - M. A. Ataalah, Abdurezzag (2019)
Lean manufacturing is one of the approaches widely used by manufacturing companies worldwide to improve business performance. Lean manufacturing could assist organisations to reduce waste, minimize cost, and improve workflow. Unfortunately, very few studies have been found focusing on the Lean Manufacturing implementation in Libya. The main objective of this research was to develop a new Lean Manufacturing (LM) Model towards improving Business Performance (BP) with mediating effect of People Development (PD) and Process Improvement (PI) in Libyan companies. To achieve this aim, the research approach adopted was quantitative method. Survey was used as the research method and data was collected using questionnaire. The respondents involved General Managers, Quality Managers, Operations Managers, Production Managers, and Maintenance Managers. 320 questionnaires were returned yielding 61.5 percent response rate. The findings of the survey were analysed using Statistical Package for Social Science (SPSS) and Partial Least Square (PLS) based Structural Equation Modelling (SEM) software. The hypotheses were tested to establish the relationships between Lean Manufacturing implementation and Business Performance as well as determine the mediating effect of People Development and Process Improvement. The result was that, People Development has a positive relationship between Lean Manufacturing with Business Performance as a mediator, whilst the Process Improvement was non-supportive to the relationship between Lean Manufacturing and Business Performance in the manufacturing companies in Libya. The results of this study can hopefully be useful and act as a guide for the Libyan manufacturing compliance managers and practitioners to improve the Business Performance through LM implementation.